Disaster Risk Perception and Household Disaster Preparedness: Lesson Learned from Tsunami in Banten. Issue 1 (March 2020) - Akbar, Z; Suryaratri, R D; Tri, Y; Gumelar, G; Ariyani, M
Abstract: This research aims to determine the effect of disaster risk perception on disaster preparedness for families on the coast of Sumur district, Pandeglang, Banten. Participants in this research are families who live in coastal area consisting of father or mother in each family. Total respondents were 174 people, all of them were victims of Banten tsunami. The measuring tool used in this research is the disaster risk perception that will be measured using the Risk Perception Belief for Disaster measurement tool that was used in the National Health Survey Risk Perception (NSHRP) in 2012 and further developed by Yong (2017). Disaster preparedness will be measured using instruments based on the grievances that have been put forward by Indonesian Institute of Sciences (LIPI) and Unesco regarding disaster preparedness. This research approach is a quantitative approach using the test of influence. The results found that there is positive influence between disaster risk perception on disaster preparedness on families in the coastal Sumur district (F = 28.23; p = 0.000 <0.05). The effect of Disaster Risk Perception on Disaster Preparedness is 14.1%. There is a significant influence between the disaster risk perception to disaster preparedness on the family in the coast of Sumur District, Pandeglang. If the disaster risk perception is high, the disaster preparedness will also increase. The implications of the results of this research are research subjects who have a high disaster risk perception, meaning that the community has the value of trust that the place they live has a risk of natural disasters and finally feels they have high responsibility, control, acceptance and response to disaster risk, so that this will encourage the community to be able to carry out disaster preparedness.